Effect of formulation variables on insulin localisation within solid lipid nanoparticles - Thong, Li Ming (2016)
There has been a lot of interest on solid lipid nanoparticles (SLNs) as these colloidal submicron drug dosage forms present a promising frontier in drug delivery. It is possible to incorporate susceptible drugs such as protein intended for oral delivery. Here, we aim to develop an oral delivery system based on SLNs to deliver the peptide hormone, insulin using the double emulsion (W/O/W) solvent evaporation technique for formulating the SLNs. The choice of lipids was carefully selected to incorporate acceptability to biological milieu. The main purpose of the work was to formulate SLNs to achieve different localisation of insulin within the SLNs, based on the three hypothetical models proposed by Muller et al. (2000). Following that, the effect of this localisation on the propensity of the SLNs to be taken up by absorptive cells was investigated. SLNs was successfully fabricated to achieve two insulin localisation models, namely the solid solution model and the core-shell model with drug-enriched shell. The zeta potential measurements was used to indirectly indicate the appropriate insulin localisation model. The zeta potential of the unloaded SLNs, insulin-loaded SLNs and surface-adsorbed insulin SLNs were recorded as -51.7 ± 1 mV, -45.8 ± 1 mV and -40.8 ± 1 mV respectively. In vitro cell studies showed a notable difference in the Caco-2 cell lines when the cells were exposed to SLNs of the two different insulin localisation models. Thus, different effects seen on the Caco-2 cells suggests that the localisation of insulin within SLNs can potentially influence its uptake, stressing the importance of characterising drug localisation in nanoparticles, as this eventually affects drug bioavailability.